New approach for monitoring of nuclear material in nitric acid solution using 14N(n, γ)15N reaction. (December 2017) - Sekine, Megumi; Tomikawa, Hirofumi
Abstract: At a PUREX reprocessing facility, HNO3 solution with dissolved spent fuel, such as fission products (FP) and nuclear materials, flows in pipes and stores in tanks. To detect and deter the theft of nuclear materials from the aqueous process, measuring the 10.8 MeV gamma rays emitted by the 14 N(n, γ) 15 N reaction activated by spontaneous neutrons from, for example, 242 Cm, 244 Cm, 238 Pu, 240 Pu, and 242 Pu in nitric acid solution with dissolved spent fuel might be useful for continuous monitoring of liquid flow from the viewpoint of safeguards. In general, because high-dose gamma rays emitted from FPs are dominant below 3 MeV, it is expected that the 10.8 MeV peak would not be affected by the FP peaks. As the first step, a measurement configuration was simulated by PHITS code based on 5.3 and 10.8 MeV gamma rays activated by neutrons from a 252 Cf source. In this paper, optimization of the detector and measurement system are reported.